The Influence of Knowledge About Nutrition on Anemia Status In Adolescent Women: Pengaruh Pengetahuan Tentang Gizi Terhadap Status Anemia Pada Remaja Putri - Muliani, Resty Himma; Rakhimah, Fitriana (Universitas Muhammadiyah Sidoarjo, 2024)
Nutrition knowledge is the ability of a person to know how to choose food ingredients and consume them well every day. Nutritional status is the condition in which a person's nutrition is realized in the form of a variable, namely nutritional status, which can be in the form of poor nutritional status, deficient nutritional status, good nutritional status, and over-nutrition status as well as obesity. Lack of knowledge about the nutritional role of various types of food will create health and productivity problems for teenagers, especially young women who will later become mothers-to-be. Nutrition knowledge provides a foundation for teenagers to meet their nutritional needs and be able to improve their nutritional status because they will know the relationship between the food they consume and their nutritional status. This research is a type of quantitative research to find out the relationship between knowledge about nutrition and anemia status in adolescent girls. The research design was cross-sectional which was carried out on class IX teenage respondents at Bulakamba Brebes Vocational School, the analysis used was chi-square, and if it did not meet the requirements it would be replaced with Mann Whitney. The results of the Maan Whitney analysis showed a p-value of 0.031, which means there is an influence between the level of knowledge of teenagers about nutrition. on the incidence of anemia in adolescent girls.